Impact of COVID-19 on access to cancer care in Rwanda: a retrospective time-series study using electronic medical records data - Dale A Barnhart; Fredrick Kateera; Megan Murray; Gregory Jerome; Bethany Hedt-Gauthier; Emilia Connolly; Chiyembekezo Kachimanga; Jean Claude Mugunga; Fernet Leandre; Jesús Peinado; Alphonse Nshimyiryo; Mary Clisbee; et al. (BMJ Open)
Introduction The COVID-19 pandemic has caused disruptions in access to routine healthcare services worldwide, with a particularly high impact on chronic care patients and low and middle-income countries. In this study, we used routinely collected electronic medical records data to assess the impact of the COVID-19 pandemic on access to cancer care at the Butaro Cancer Center of Excellence (BCCOE) in rural Rwanda.Methods We conducted a retrospective time-series study among all Rwandan patients who received cancer care at the BCCOE between 1 January 2016 and 31 July 2021. The primary outcomes of interest included a comparison of the number of patients who were predicted based on time-series models of pre-COVID-19 trends versus the actual number of patients who presented during the COVID-19 period (between March 2020 and July 2021) across four key indicators: the number of new patients, number of scheduled appointments, number of clinical visits attended and the proportion of scheduled appointments completed on time.Results In total, 8970 patients (7140 patients enrolled before COVID-19 and 1830 patients enrolled during COVID-19) were included in this study. During the COVID-19 period, enrolment of new patients dropped by 21.7% (95% prediction interval (PI): −31.3%, −11.7%) compared with the pre-COVID-19 period. Similarly, the number of clinical visits was 25.0% (95% PI: −31.1%, −19.1%) lower than expected and the proportion of scheduled visits completed on time was 27.9% (95% PI: −39.8%, −14.1%) lower than expected. However, the number of scheduled visits did not deviate significantly from expected.Conclusion Although scheduling procedures for visits continued as expected, our findings reveal that the COVID-19 pandemic interrupted patients’ ability to access cancer care and attend scheduled appointments at the BCCOE. This interruption in care suggests delayed diagnosis and loss to follow-up, potentially resulting in a higher rate of negative health outcomes among cancer patients in Rwanda.